Kontribusi Kepercayaan Diri Dan Motivasi Terhadap Kemampuan Berbicara Di Depan Umum Mahasiswa Politeknik Negeri Lampung Pada Mata Kuliah Bahasa Indonesia - Upy Raudotul Jannah; Refdi Akmal; Maisuri Hardani (Departement of Mathematics Education, 2023)
This research was motivated by the lack of students' ability to express their opinions in public, especially in Indonesian language courses. Apart from that, students did not achieve the expected competency at each meeting. Based on the background of the problem, the causes of students' lack of ability to speak in public were formulated. Is there a contribution between self-confidence and motivation and students' public speaking abilities? This research uses descriptive-correlational research methods. The subjects of this research were Lampung State Polytechnic students taking Indonesian language courses. The sample of this research was 60 students. The data in this research was taken using questionnaire and interview techniques. Hypothesis testing is carried out using simple and multiple linear regression formulas. Based on the results of data analysis, the results of multiple regression analysis of variables X1 and Variable X2 with variable Y. value T-table self-confidence and motivation 6.23 and 5.12. The significance level is 0.000 and the t table is 1.98, this means tcount > ttable so Ha is accepted, meaning the regression coefficient is significant. Thus, it can be concluded that there is a significant contribution to self-confidence and motivation.